Supporting the mental health of dietetic students : perspectives from work-integrated learning supervisors : a thesis presented in fulfilment of the requirements for the degree of Master of Science (Human Nutrition), Massey University, Albany, New Zealand - Soniassy, Reena (Massey University, 2023)
Background: Universities worldwide are becoming increasingly aware of student mental health. Anecdotal information gathered from dietetic educators at Massey University has indicated that work-integrated learning (WIL) is highly stressful for some students, with achievement of competency on placement significantly hindered by their mental health. Research thus far has focussed on student perspectives. However, supervisors play a key role in supporting WIL, coaching students, and assessing performance. Therefore, this current study aimed to explore workplace supervisors’ perceptions of student mental health and wellbeing during their WIL programme and their role in supporting students in this context. Methods: An exploratory mixed-method approach was used to conduct a two-phased study. Firstly, a quantitative online survey (n = 80; 60%) was sent to 133 supervisors from the Massey University MSc (Nutrition and Dietetics) WIL programme and results analysed using descriptive statistics and correlation analysis. Secondly, semi-structured recorded interviews (n = 11) were undertaken with a sample of survey respondents. Professionally transcribed data were analysed using thematic analysis to evaluate supervisor experiences. Results: Supervisors noted variability among students, with some mentally thriving during WIL, but more others significantly struggling, and many being influenced across individual-, relationship- and organisational levels. However, most supervisors (69%) only felt ‘somewhat confident’ or ‘not confident at all’ in recognising signs of anxiety and depression. Almost all (92%) had no formal mental health training. The supervisory relationship was identified as an important influence (positive and negative) on student mental health and wellbeing. Conclusions: Key approaches described by supervisors to support student mental health and wellbeing during WIL include the creation of a sense of belonging for students within the workplace, using appropriate supervisory styles which align with mentoring and coaching techniques, adopting culturally responsive supervision and allocating dedicated or consistent supervisors for each student. Potential strategies to support workplace supervisors in their role were also identified, such as mental health first aid and resilience training.
Figures 2.2 (=Froehlich Chow & Humbert, 2014 Fig 1), 2.4 (Patten & Vaterlaus, 2021, Fig 1) & 2.11 (Walsh et al., 2020 Fig 3) were removed form copyright reasons. Figure 2.3 is reused under a CC BY 4.0 Deed Attribution 4.0 International license.
Keywords: 520304 Health psychology; 321099 Nutrition and dietetics not elsewhere classified